Analysis on the Development of Wind-assisted Ship Propulsion Technology and Contribution to Emission Reduction. Issue 1 (January 2022) - Wang, Yunlong; Zhang, Xin; Lin, Shaochuan; Qiang, Zhaoxin; Hao, Jinfeng; Qiu, Yan
Abstract: With the issue of peaking carbon dioxide emissions and carbon neutrality increasingly becoming the forefront of international public opinion, changes in the shipping industry are imminent and destined to cause long-term transformation across the entire industry chain, from ship design to maritime operations. Wind energy as a clean energy source has attracted the increasing attention of experts in the shipping field. This paper summarizes the application and development of wind-aided navigation technology for ships represented by rotors, towing kites, wing sails and soft sails, and analyses the constraints of wind-aided navigation technology. The contribution to emission reduction of typical wind-aided navigation methods such as rotors, towing kites, wing sails and soft sails is summarized. Finally, the development suggestions of wind-assisted ship propulsion (WASP) technology are summarized and proposed, which can provide reference for further research and application of this technology.